Answer:
![\Large\boxed{f(x-1)=x}](https://img.qammunity.org/2023/formulas/mathematics/high-school/onkk5njmegba7eabnjjl9ioou8abtx1qnf.png)
Explanation:
Given function
f(x + 1) = x + 2
Isolate [ x + 1 ] on the right-hand side
f(x + 1) = x + 1 + 1
f(x + 1) = (x + 1) + 1
Substitute [ x + 1 ] with x
f(x) = x + 1
Substitute [ x ] with [ x - 1 ]
f(x - 1) = (x - 1) + 1
![\Large\boxed{f(x-1)=x}](https://img.qammunity.org/2023/formulas/mathematics/high-school/onkk5njmegba7eabnjjl9ioou8abtx1qnf.png)
Hope this helps!! :)
Please let me know if you have any questions